2015
DOI: 10.1007/s12035-015-9384-y
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin Intracerebroventricular-Induced Neurotoxicity and Brain Insulin Resistance: a Therapeutic Intervention for Treatment of Sporadic Alzheimer’s Disease (sAD)-Like Pathology

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder that is remarkably characterized by pathological hallmarks which include amyloid plaques, neurofibrillary tangles, neuronal loss, and progressive cognitive loss. Several well-known genetic mutations which are being used for the development of a transgenic model of AD lead to an early onset familial AD (fAD)-like condition. However, these settings are only reasons for a small percentage of the total AD cases. The large majorities of AD cases are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 149 publications
6
61
0
1
Order By: Relevance
“…The impaired memory of the ICV-STZ rats might be attributed to the loss of functional synapses or subtle changes in both the magnitude and distribution of effective synaptic coupling without causing substantial synapse loss1753. Insulin receptors distribute at synapses and are extremely abundant in areas of rich synaptic density such as the cortex and hippocampus, suggesting a possible relationship between insulin signaling and synaptic plasticity12. In the present study, we found a modest increase in synapsin1, not synaptophysin or PSD-95, in the intranasal insulin treated ICV-STZ rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impaired memory of the ICV-STZ rats might be attributed to the loss of functional synapses or subtle changes in both the magnitude and distribution of effective synaptic coupling without causing substantial synapse loss1753. Insulin receptors distribute at synapses and are extremely abundant in areas of rich synaptic density such as the cortex and hippocampus, suggesting a possible relationship between insulin signaling and synaptic plasticity12. In the present study, we found a modest increase in synapsin1, not synaptophysin or PSD-95, in the intranasal insulin treated ICV-STZ rats.…”
Section: Discussionmentioning
confidence: 99%
“…Rats that received an intracerebroventricular administration of streptozotocin (ICV-STZ), develop several Alzheimer-like pathological changes and behavioral abnormalities, and have been used as a sporadic Alzheimer’s rat model12. More widely known as a diabetogenic substance, STZ causes severe neuronal dysfunction when injected into the brain at a subdiabetogenic dose that does not affect the glucose level in the brain12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, STZ also results in inhibiting Akt/PKB and insulin receptor signaling pathways, and then insulin resistance in the brain. Inhibition of PI3K and AKT also activates the glycogen synthase‐3β which promotes the Aβ accumulation and Tau hyperphosphorylation, in turn, leading to the degeneration of synapse and even neurons . In addition, glucose deficit in the brain could activate the p38 mitogen‐activated protein kinase pathway, cause memory impairments, synapse dysfunction and increase the level of Tau phosphorylation .…”
Section: Metabolic Damage Modelsmentioning
confidence: 99%
“…Inhibition of PI3K and AKT also activates the glycogen synthase-3β which promotes the Aβ accumulation and Tau hyperphosphorylation, in turn, leading to the degeneration of synapse and even neurons. 47 In addition, glucose deficit in the brain could activate the p38 mitogen-activated protein kinase pathway, cause memory impairments, synapse dysfunction and increase the level of Tau phosphorylation. 48 On the basis of the observations, scientists have established the sAD animal models induced by STZ.…”
Section: Streptozotocin-induced Ad Animal Modelmentioning
confidence: 99%